Development, validation and a GAPI greenness assessment for the determination of 103 pesticides in mango fruit drink using LC-MS/MS - Tippannanavar, Madhu; Banerjee, Tirthankar; Shekhar, Sumit; Sahu, Sudama Ram; Singh, Bijendra; Narayanan, Neethu; Rudra, Shalini Gaur; Chakrabarti, Bidisha; Gupta, Suman; Singh, Anupama (Frontiers in Chemistry, 2023)
A robust method was developed using LC-ESI-MS/MS-based identification and quantification of 103 fortified pesticides in a mango fruit drink. Variations in QuEChERS extraction (without buffer, citrate, and/or acetate buffered) coupled with dispersive clean-up combinations were evaluated. Results showed 5 mL dilution and citrate buffered QuEChERS extraction with anhydrous (anhy) MgSO4 clean-up gave acceptable recovery for 100 pesticides @ 1 μg mL−1 fortification. The method was validated as per SANTE guidelines (SANTE/11813/2021). 95, 91, and 77 pesticides were satisfactorily recovered at 0.1, 0.05, and 0.01 μg mL−1 fortification with HorRat values ranging from 0.2–0.8 for the majority. The method showed matrix enhancement for 77 pesticides with a global uncertainty of 4.72%–23.89%. The reliability of the method was confirmed by real sample analysis of different brands of mango drinks available in the market. The greenness assessment by GAPI (Green Analytical Procedure Index) indicated the method was much greener than other contemporary methods.